Purine metabolism during neuronal differentiation: the relevance of purine synthesis and recycling. (18th August 2013) - Göttle, Martin; Burhenne, Heike; Sutcliffe, Diane; Jinnah, H. A.
Abstract Purines are a class of small organic molecules that are essential for all cells. They play critical roles in neuronal differentiation and function. Their importance is highlighted by several inherited disorders of purine metabolism, such as Lesch–Nyhan disease, which is caused by a deficiency of the purine salvage enzyme, hypoxanthine‐guanine phosphoribosyltransferase (HGprt). Despite the known importance of purines in the nervous system, knowledge regarding their metabolism in neurons is limited. In the current studies, purine pools and their metabolism were examined in rat PC6‐3 cells, a PC12 pheochromocytoma subclone that undergoes robust differentiation with nerve growth factor. The results were compared with five new independent PC6‐3 subclones with defective purine recycling because of different mutations affecting HGprt enzyme activity. The results demonstrate an increase in most purines and in energy state following neuronal differentiation, as well as specific abnormalities when purine recycling is lost. The loss of HGprt‐mediated purine recycling also is associated with significant loss of dopamine and related metabolites in the mutant PC6‐3 lines, suggesting an important connection between purine and dopamine pathways. These results provide insights into how purine pools and metabolism change with neuronal differentiation, and how specific enzyme defects may cause neuronal dysfunction. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> Differentiation of dopaminergic PC6‐3 cells is accompanied by increased purine pools and energy state. The lack of a functional purine recycling pathway causes purine limitation in both undifferentiated and differentiated cells, as well as profound loss of dopamine content. The results imply an unknown mechanism by which intracellular purine levels regulate dopamine levels.